2015
DOI: 10.1210/er.2015-1034
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Receptor- and Tissue-Specific Actions in Androgen Signaling

Abstract: The physiological androgens testosterone and 5α-dihydrotestosterone regulate the development and maintenance of primary and secondary male sexual characteristics through binding to the androgen receptor (AR), a ligand-dependent transcription factor. In addition, a number of nonreproductive tissues of both genders are subject to androgen regulation. AR is also a central target in the treatment of prostate cancer. A large number of studies over the last decade have characterized many regulatory aspects of the AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 283 publications
(317 reference statements)
0
73
0
Order By: Relevance
“…Genome-wide analyses have revealed that, by and large, AR regulates transcription via AR-binding sites (ARBs) in distal enhancers instead of binding to promoter regions (Pihlajamaa et al, 2015;Tang et al, 2011). In addition to androgen response elements (AREs) in the ARBs, the region of AR chromatin occupancy encompasses cis-elements for other transcription factors (TFs), such as pioneer TFs GATA-binding protein 2 (GATA2) and forkhead box A1 (FOXA1), E twenty-six or E26 transformation-specific (ETS) TFs and homeodomain protein HOXB13 (Carroll et al, 2005;Sahu et al, 2011;Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide analyses have revealed that, by and large, AR regulates transcription via AR-binding sites (ARBs) in distal enhancers instead of binding to promoter regions (Pihlajamaa et al, 2015;Tang et al, 2011). In addition to androgen response elements (AREs) in the ARBs, the region of AR chromatin occupancy encompasses cis-elements for other transcription factors (TFs), such as pioneer TFs GATA-binding protein 2 (GATA2) and forkhead box A1 (FOXA1), E twenty-six or E26 transformation-specific (ETS) TFs and homeodomain protein HOXB13 (Carroll et al, 2005;Sahu et al, 2011;Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pascual-Le Tallec and coworkers (Pascual-Le Tallec et al 2003) reported promoter dependence for MR corepression by PIAS1, and Yang and coworkers (Yang et al 2014(Yang et al , 2015 reported gene-specific effects for GEMIN4, XRCC6, EEF1A1 and SSRP1. These differences may be mediated by other transcription factors including so-called pioneer/licensing factors such as FOXAI which have been extensively characterized for steroid receptors particularly the AR (Pihlajamaa et al 2015). Large-scale gene expression profiling and coactivator recruitment assays for novel progesterone receptor modulators have also found that regulation is highly gene specific despite a common coactivator recruitment profile for certain compounds (Berrodin et al 2009).…”
Section: Gene Specificitymentioning
confidence: 99%
“…These binding sites are characterized by cofactors and by pioneering factors like AP-2, FoxA1 and GATA3. Pioneering factors are proteins which facilitate the binding of nuclear receptors to their targets by opening up the chromatin, without them the binding is greatly diminished (17,18). Further cofactors are recruited following ER binding.…”
Section: Ermentioning
confidence: 99%
“…Further cofactors are recruited following ER binding. ER binds to the estrogen response elements (ERE) located in promotors (18) or distal sites from where ER interacts with targets by chromatin looping (17). In the non-classical genomic pathway, phosphorylated ER can act independently of ligands, as a response to p38 MAPK, JNK or PI3K/AKT signaling.…”
Section: Ermentioning
confidence: 99%
See 1 more Smart Citation